Health-Related Quality of Life (HRQoL) in Idiopathic Inflammatory Myopathy: A Systematic Review - Leclair, V.; Regardt, M.; Wojcik, S.; Hudson, M.; Canadian Inflammatory Myopathy, Study (PLoS One, 2016)
Health-related quality of life (HRQoL) is a research priority in chronic diseases. We undertook a systematic review (registration #CRD42015024939) to identify, appraise and synthesize the evidence relating to HRQoL in idiopathic inflammatory myopathies (IIM). A comprehensive search was conducted in August 2015 using CINAHL, EMBase and Pubmed to identify studies reporting original data on HRQoL in IIM using generic HRQoL instruments. Characteristics of samples and results from selected studies were extracted and appraised using a standardized approach. Qualitative synthesis of the results was performed. Ten studies including a total of 654 IIM subjects were included in this systematic review. HRQoL was significantly impaired in all subsets of IIM compared with the general population. Disease activity, disease damage and chronic disease course were associated with poorer HRQoL. Insufficient or conflicting results were found in associations between clinical features, treatment, disease duration and mood or illness perception, and HRQoL in IIM. This study suggests that HRQoL is impaired in IIM. However, due to the paucity and heterogeneity of the evidence to date, robust estimates are lacking and significant knowledge gaps persist. There is a need for studies that systematically investigate the correlates and trajectory of HRQoL in IIM.